Battlesight zero in context of counter UAV engagement - Pemčák, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This paper explores the optimal zeroing distance for an assault rifle on the modern battlefield. Traditionally, armies have used sight settings that align the projectile’s trajectory with the line of sight at distances of 25 m and 300 m. This configuration is well suited for assault rifles chambered in 7 mm to 8 mm calibers when fired from the prone position at an approaching figure target. However, with the increasing use of smaller-caliber ammunition (5 mm to 6 mm) and evolving battlefield threats, including drones, it is necessary to reassess this traditional approach. This study investigates the optimal first zeroing distance when engaging both drone-type targets and standard NATO Type E figure targets. All tests and configurations were conducted using the BREN 2 assault rifle used by the Czech Army. Methods: This study uses probability-of-hit simulation methods. The parameters of the BREN 2 weapon under investigation were experimentally verified. Results: The probability of hitting a point target depends significantly on the setting of the sight zeroing distance. The greater the deviation of the projectile trajectory from the line of sight, the lower the probability of hitting the target without distance adjustment. Conclusion: The findings suggest that for engaging small, irregular targets such as UAVs, zeroing distances between 50 m and 100 m are more effective, without compromising combat effectiveness against standard figure targets.